Determinants of user acceptance of wearable IoT devices. Issue 1 (31st December 2022) - Suhluli, Salem Ali; Ali Khan, Syed Md. Faisal
Abstract: The Internet of Things (IoT) has modified our daily lives. This study examines the relationship between behavioural intention towards adoption of IoT wearable devices (WIoT) in the context of social norms, privacy, security concerns, and trust. The current study consists of a review of the literature for constructing the theoretical framework of the study and subsequently, survey was conducted from 200 respondents from Saudi Arabia was conducted between 2020 and 2020. The statistical results illustrate that the proposed model fits well for the current study and conclude that perceived privacy risks and health awareness have a significant impact on the intention to adopt wearable devices, whereas the social norms have a negative effect on the privacy and security concerns towards the use of WIoT devices. The study also helps to improve the predictability of user intention to use IoT devices